Polygamy in the Perspective of Christianity - Novia Helda Rompis (Estudiante Law Journal, 2020)
This study aims to find out how the sociological purpose of polygamy in the perspective of Christianity itself in social life knowing that based on Christianity itself polygamy is prohibited, it does not mean that there is no polygamy in Christianity, but if you look at it historically in the Bible which divided into two parts, namely in the old agreement and the new agreement there are several explanations about how polygamy can exist and then become a prohibition. The type of research used is empirical law (sociological), using legal research material sources consisting of primary law and secondary law. The technique of collecting legal materials is done by interviewing and observing. then processed based on the topic of the problem that has been formulated based on the formulation of the problem in this study. These study, based on the formulation of the problem where there is a problem of polygamy in Christianity, the influencing factors, and the sanctions imposed on people who carry out polygamous marriages. Therefore, many polygamists do not understand correctly the meaning of polygamous marriage itself and the existing requirements of existing national law and church law and the impact it has, which in Christianity itself initially adhered to monogamy as stated on the Marriage Act, one for all time. Keywords: Polygamy, Christianity, Perspective, Religion